New Record of Aphytis melinus Debach, 1959 as a Parasitoid on the Oriental Yellow Scale Aonidiella orientalis in Iraq and its Seasonal Occurrence in Al-Suwaira Region and Al-Qanat Region - Khamas, Alaa A.; Hassan, Bassim H.; Meshjel, Maysoon H. (Iraqi Journal of Science, 2026)
The oriental yellow scale insect (Aonidiella orientalis) (Newstead, 1894) was studied as a harmful pest affecting citrus trees in the Al-Qanat (Baghdad) and Al-Suwaira (Wasit) during the 2023–2024 seasons. This study reports the first record of the external parasitoid Aphytis melinus DeBach, 1959 in Iraq, based on morphological characterization of adult traits and pigmentation patterns of A. melinus pupae, consistent with molecular identification results using the COI gene fragment. The genetic analysis revealed a 99% match with a globally recorded strain in France (GenBank accession number KX065209) compared to the local strain registered in GenBank under the accession number PP301406.The study also investigated the impact of climatic factors on the seasonal distribution of the pest and its parasitoid. The highest pest density was recorded between September and January, with the lowest densities observed in May and June. The peak parasitism rate was recorded in October (1.25%). Climatic factors showed significant effects, with a negative correlation between temperature and each pest and parasitoid densities, while the increase in the parasitoid numbers correlated positively with relative humidity